Philosophy and economic theory - Hahn, Frank (ed.); Hollis, Martin (ed.) (New York, 1979)
The aim of this series is to bring together important recent writings in major areas of philo sophical inquiry, selected from a variety of sources, mostly periodicals, which may not be conveniently available to the university student or general reader. The editor of each volume contributes an introductory essay on the items chosen and on the questions with which they deal. A selective bibliography is appended as a guide to further reading. FRANK HAHN is Professor of Economics at Cambridge University and MARTIN HOLLIS is Senior Lecturer in Philosophy at the University of East Anglia.
Keywords: Economic addresses